First estimates of population size and home range of Caribbean reef and nurse sharks using photo-identification and BRUVS - Kohler, Johanna; Gore, Mauvis; Ormond, Rupert; Austin, Timothy (Frontiers in Marine Science, 2023)
The assessment of parameters population size and individual home range is important for effective conservation management of sharks. This study uses the novel application of photo identification (photo-ID) to BRUVS footage as a non-invasive alternative to tagging in order to generate individual capture histories. These were used in mark-recapture models to estimate effective population sizes and to determine home ranges. In the Cayman Islands a total of 499 shark sightings of six coastal shark species were recorded on BRUVS from 2015 - 2018, but re-sighting rates were only sufficient for the determination of population parameters for two species - Caribbean reef shark (Carcharhinus perezi) and nurse shark (Ginglymostoma cirratum). The calculated super-population sizes for Caribbean reef shark (180 ± 37 SE) and nurse shark (336 ± 61 SE) were greater than the estimates for each species based on a closed-population model (Caribbean reef shark: 128 ± 40 SE, nurse shark: 249 ± 48 SE), though both measures indicated that there were about twice as many nurse sharks (1.3 - 1.8 sharks/km2) as Caribbean reef sharks (0.7 – 1 shark/km2) within the study area. The demographic compositions included numerous immature individuals, indicating that breeding of both species takes place within the study area of 188 km2. Most recognizable individuals of both species showed linear home ranges of <20 km, but a few individuals were observed to have moved longer distances (Caribbean reef shark: 125.37 km, nurse shark: 156.07 km). The data indicate that the home ranges and long-distance movements of individual sharks observed within the islands’ marine protected areas (MPAs) often extend to areas beyond the MPA’s boundary, potentially exposing them to fishing activities. This study provides the first estimates of population size for Caribbean reef and nurse sharks in the Cayman Islands and the first estimate of a Caribbean reef shark population globally.